JOURNAL OF GOVERNMENT & POLITICS : Cultural Dimensions Toward the Government Communications in the Policy of Street Vendors Relocation at Yogyakarta City - La Mani , Budi Guntoro (FISIPOL UMY, 2016)
The increasing population of street vendors implicates to the dynamics and models of governments regulation in urban areas.